2020
DOI: 10.1016/j.bone.2020.115321
|View full text |Cite
|
Sign up to set email alerts
|

Hip load capacity and yield load in men and women of all ages

Abstract: Quantitative computed tomography (QCT) based finite element (FE) models can compute subject-specific proximal femoral strengths, or fracture loads, that are associated with hip fracture risk. These fracture loads are more strongly associated with measured fracture loads than DXA and QCT measures and are predictive of hip fracture independently of DXA bone mineral density (BMD). However, interpreting FE-computed fracture loads of younger subjects for the purpose of evaluating hip fracture risk in old age is cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…There were also a limited number of covariates considered for this work; in addition to age, sex, BMI, and LEF AGES-I it may have been of interest to test other comorbidities, biometrics, or psychosocial factors in our models 45 . Likewise, as the AGES-Reykjavík study was almost entirely comprised of Caucasian subjects 46 , these findings may not be generalizable to other races or ethnicities.…”
Section: Discussionmentioning
confidence: 88%
“…There were also a limited number of covariates considered for this work; in addition to age, sex, BMI, and LEF AGES-I it may have been of interest to test other comorbidities, biometrics, or psychosocial factors in our models 45 . Likewise, as the AGES-Reykjavík study was almost entirely comprised of Caucasian subjects 46 , these findings may not be generalizable to other races or ethnicities.…”
Section: Discussionmentioning
confidence: 88%
“…However, the Drucker–Prager yield criterion 55 , which is an approximation to the Mohr–Coulomb law and a modification of the Von Mises yield criterion, is applied in some studies modelling bone as a brittle material with isotropic material properties 52 , 53 . The distortion energy failure theory applied in our study has also been widely used since its validation as a robust theory for bone failure when using elastic–plastic and isotropic material properties for bone 16 , 33 , 43 , 54 . Warden et al 43 calculated femoral strength considering heterogeneous and non-linear post-yield material properties under a compressive load that was applied by an incremental displacement on the femoral head.…”
Section: Discussionmentioning
confidence: 99%
“…They computed the element stress and strain, using individual element’s stress–strain relationship, similar to the relations used in this study, in conjunction with the von Mises yield criterion 43 . Most recently, a study measured hip load capacity using elastic–plastic and isotropic modeling of bone in conjunction with the distortion energy yield criterion 54 .…”
Section: Discussionmentioning
confidence: 99%
“…However, over‐adapted femora are particularly fragile under sideways falls, 33 especially in the elderly. A recent experiment has shown that the stance load capacity of the femur is greater than sideways fall load capacity 21 . The trabecular bone undergoes changes in bone characteristics earlier than cortical bone during the onset of osteoporosis 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Loading and boundary conditions were applied to each FE model of the proximal femur to simulate the sideways fall and stance configurations, similar to previous studies 16‐19 . To evaluate the intrinsic mechanical behavior of the proximal femur, each FE model was placed under a standard “virtual testing” configuration (either stance or sideways fall) and loaded with the same force 8,16,20,21 . For the sideways fall configuration, a load of 300N was vertically applied to the femoral head when the femoral shaft was tilted at 10° with respect to the ground and the femoral neck was internally rotated by 15°; the distal end of the femur was fully restrained (Fig.…”
Section: Methodsmentioning
confidence: 99%